Qualitative Phytochemical Analysis and Antibacterial Activity Evaluation of Indian Terminalia spp. Against the Pharyngitis causing pathogen Streptococcus pyogenes - Wright, Mitchell Henry; Arnold, Megan Sarah Jean; Lee, Cameron Jay; Courtney, Reece; Greene, Anthony Carlson; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Streptococcus pyogenes is a gram-positive, pathogenic bacterium which causes a variety of diseases including streptococcal phar- yngitis, impetigo and rheumatic heart disease, depending on which tissue it infects. Many Terminalia spp. have documented therapeutic properties as general antiseptics, inhibiting the growth of a wide variety of bacterial species. Methods: Solvent extracts were prepared using Indian Terminalia spp. with documented ethnobotanical usage to treat bacterial infections, or published antibacterial activity. The extracts were investigated by disc diffusion assay for the ability to inhibit the growth of a clinical strain of S. pyogenes. Their MIC values were determined to quantify and compare their efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: T. arjuna, T. catappa and T. chebula methanolic and ethyl acetate extracts displayed potent antibacterial activity in the disc diffusion assay against S. pyogenes. The T. catappa and T. chebula ethyl acetate extracts were particularly potent, with MIC values of 225 and 205 µg/mL respectively. All methanolic extracts were also potent growth inhibitors with MIC values of 268 µg/mL (T. arjuna methanolic extract), 425 µg/mL (T. catappa methanolic extract) and 300 µg/mL (T. chebula meth- anolic extract). The T. catappa hexane extract was also a potent S. pyogenes growth inhibitor (MIC 768 µg/mL). All other extracts were either ineffec- tive or were of only low efficacy. Furthermore, all of the Indian Terminalia spp. extracts were nontoxic in the Artemia fransiscana bioassay, with LC50 values >1000 µg/mL. Conclusion: The potent growth inhibitory bio- activity of the methanolic and ethyl acetate T. arjuna, T. catappa and T. chebula extracts against S. pyogenes demonstrates their potential for the treatment and prevention of pharyngitis, impetigo and rheumatic heart disease. All extracts were nontoxic indicating their safety for ther- apeutic use.
Keywords: Terminalia arjuna; Terminalia catappa; Terminalia chebula phar- yngitis; Impetigo; Rheumatic heart disease; Antibacterial activity; Ayurveda.